Transport Properties of A Quasi-two-dimensional Electron Gas in InP/In\(_{1 - x}\)Ga\(_{x}\)As/InP Quantum Wells : Correlation and Magnetic Field Effects - Khanh, Nguyen Quoc; Huyen, Mai Thanh (Communications in Physics, 2015)
We investigate correlation and magnetic field effects on the mobility and resistivity of a quasi-two-dimensional electron gas in an InP/In\(_{1 - x}\)Ga\(_{x}\)As/InP quantum well at arbitrary temperatures. We study the dependence of the mobility and resistivity on the carrier density, magnetic field, layer thickness and temperature for alloy disorder and impurity scattering using different approximations for the local-field correction. Multiple scattering effects and discuss the possibility of a metal-insulator transition, which might happen at low density for unpolarized and fully polarized electron gas are also considered